Perbandingan Perlakuan Berbagai Jenis Pisang dan Jenis Coating terhadap Kualitas dan Sensori Dried Banana - Putri, Anindya N; Herawati, Maria M (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Dried banana is processed banana fruit with its moisture content removed by drying, either naturally or using a special tool (food dehydrator), without removing the original flavor and aroma of the banana fruit. Three banana varieties were used in this study: “tanduk” banana, “kepok” banana, and “susu” banana. Coatings were also added to determine the best coating between artificial and natural sweeteners. The artificial sweetener was saccharin, while the natural sweetener was longan honey. This study aimed to find suitable varieties for dried bananas and appropriate coatings based on chemical and consumer preferences through sensory analysis (organoleptic). The analysis utilized a factorial randomized block design with two factors: banana variety and coating type, resulting in nine treatments and three replications. The nine treatments consisted of P1C0 (‘tanduk’ banana without coating), P2C0 (‘kepok’ banana without coating), P3C0 (‘susu’ banana without coating) as control, P1C1 (‘tanduk’ banana with saccharin coating), P2C1 (‘kepok’ banana with saccharin coating), P3C1 (‘susu’ banana with saccharin coating), P1C2 (‘tanduk’ banana with honey coating), P2C2 (‘kepok’ banana with honey coating), and P3C2 ( ‘susu’ banana with honey coating). Based on the research results, the best-dried banana product was the P2C2 treatment, the honey-coated kepok banana variety.